1970
DOI: 10.1128/jb.102.2.531-536.1970
|View full text |Cite
|
Sign up to set email alerts
|

Hemin-Deficient Mutants of Salmonella typhimurium

Abstract: Nine hemin-deficient mutants of Salmonella typhimurium LT2 were isolated as neomycin-resistant colonies. Five of these mutants could be stimulated by A-aminolevulinic acid (A-ALA), thus representing hemA mutants. Since S. typhimurium LT2 is not able to incorporate hemin, the identification of the mutants not stimulated by A-ALA was made on the basis of the simultaneous loss of catalase activity and cytochromes. The hemA gene was mapped by conjugation in the trp region, probably in the order purB-pyrD-hemA-trp;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1972
1972
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Colonies were selected which could grow on plates containing sodium succinate (0.2O/,, w/v) as sole carbon source, the amino acids (all a t 0.010/,, w/v) required by this strain, and 5-aminolaevulinic acid (25 pM) but not on plates deficient in this compound. One such mutant, designated A201, was chosen for further studies and the mutant allele shown to be 2-4O/, cotransducible with tryptophan, indicating that it corresponds to the hemA mutation described previously [12,13]. Strain A201 could not grow on glycerol or citric-acid-cycle metabolites unless supplemented with 6-aminolaevulinic acid : the concentration of 5-aminolaevulinic acid required to achieve growth rates equivalent to those of the parental strain on these substrates in batch culture was about 1 pM as previously described [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonies were selected which could grow on plates containing sodium succinate (0.2O/,, w/v) as sole carbon source, the amino acids (all a t 0.010/,, w/v) required by this strain, and 5-aminolaevulinic acid (25 pM) but not on plates deficient in this compound. One such mutant, designated A201, was chosen for further studies and the mutant allele shown to be 2-4O/, cotransducible with tryptophan, indicating that it corresponds to the hemA mutation described previously [12,13]. Strain A201 could not grow on glycerol or citric-acid-cycle metabolites unless supplemented with 6-aminolaevulinic acid : the concentration of 5-aminolaevulinic acid required to achieve growth rates equivalent to those of the parental strain on these substrates in batch culture was about 1 pM as previously described [12].…”
Section: Methodsmentioning
confidence: 99%
“…However, from these experiments it cannot be decided if these genes are concerned with the regulation of haem synthesis or with the synthesis of the apoprotein of a particular cytochrome. Methods for the isolation of 5-aminolaevulinic acid synthetase-deficient mutants [12,13] and mutants auxotrophic for haematin [ 14,151 have been reported for E . coli.…”
mentioning
confidence: 99%
“…Selection for neomycin resistance has been used in the isolation of hemin-deficient mutants of Escherichia coli K-12 (13) and Salmonella typhimurium (12). It was postulated that respiratory-deficient cells incorporated less neomycin than normal cells (12). One explanation for this may be the inability of these mutants to generate sufficient energy to concentrate the antibiotic.…”
mentioning
confidence: 99%
“…Mapping of hemA and hemB genes in Salmonella typhimurium LT2 showed that both have similar location to the corresponding genes in E. coli K-12 (30); this seems also to be true for at least a third hem gene in the two organisms (A. Sasarman et al, unpublished data). A relatively exhaustive mapping of hem genes in S. aureus showed that in this organism the hem loci were clustered in a single region of the chromosome (37).…”
mentioning
confidence: 90%
“…Heme-deficient mutants of bacteria are partially resistant to aminoglycoside antibiotics, which were often used for their isolation (1,2,16,29,30,31,37). The mechanisms of this resistance is not yet well established, and a diminished uptake of the drug has been suggested (30). The resistance to aminoglycoside antibiotics seems to be a common property of several types of respiratory mutants of bacteria, for menaquinone-deficient mutants of Staphylococcus aureus are also resistant to them (32).…”
mentioning
confidence: 99%